1995
DOI: 10.1038/sc.1995.24
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum lipids and indicators of adiposity in men with spinal cord injury

Abstract: Several reports indicate that dyslipidemia, primarily depressed high density lipoprotein cholesterol, is common in persons with spinal cord injury. The purpose of this study was to assess the relationships between anthropometric and near infrared interactance measure ments to the serum lipoprotein profiles of 46 men with spinal cord injury of > 6 months duration. Mean age (± SD) was 49.5 ± 15.0 Y and duration of injury was 17.5 ± 13.0 y. Forty-one percent of the subjects had low high density lipoprotein choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 30 publications
(14 reference statements)
4
70
3
Order By: Relevance
“…8,21 The present study, on the contrary, showed more favorable lipid and (apo)lipoprotein values, despite the signi®cant increase of body mass and BMI between t1 and t2. However, the lack of change in the sum of four skinfolds suggests that the change in body mass was the consequence of an increased muscle mass, instead of an increase in adipose tissue.…”
Section: Determinants Of Changes In Lipid and (Apo)lipoprotein Pro®lescontrasting
confidence: 73%
“…8,21 The present study, on the contrary, showed more favorable lipid and (apo)lipoprotein values, despite the signi®cant increase of body mass and BMI between t1 and t2. However, the lack of change in the sum of four skinfolds suggests that the change in body mass was the consequence of an increased muscle mass, instead of an increase in adipose tissue.…”
Section: Determinants Of Changes In Lipid and (Apo)lipoprotein Pro®lescontrasting
confidence: 73%
“…Three studies 11,15,63 have measured waist circumference in subjects with chronic SCI. Jeon et al 11 did not report values, nor was the method of obtaining waist circumference described.…”
Section: Body Mass Index (Bmi) As a Marker Of Obesity In Chronic Scimentioning
confidence: 99%
“…176 ± 178 Ine ective orthostatic circulatory regulation is associated with notable problems for patients with SCI and may contribute to the increased prevalence of cardiovascular disease in this population. 64 The combination of the loss of peripheral sympathetic vasomotor tone, reduce lower extremity skeletal muscle pump, attenuated venous return, and depressed baroreceptor sensitivity results in signi®cant alterations of the cardiovascular system.…”
Section: Thoracic Autonomic Dysfunctionmentioning
confidence: 99%